A Study on Consumer Value Towards Service Brands in Malaysia - Das, Sanjeeta (2008)
The past decade has remarkably proved that the world is approaching from an industrially driven economy to a people driven economy. There was an age when machines were used to be kept in the centre of decision making. But now it is the consumers who direct what decision has to be made. (Gobe, 2001). Consumers are gaining importance. They are newly in charge and wielding their power with relish (Smith, 2007).The model of a people driven economy is manifested in the power of the consumer. Brands are clearly operating with complete different set of values today than a few years ago. Where ones creation of a product and forcing it on consumers was the main motive, now has been replaced by creating a product according to the need of the consumer, to fill the vacuum in between desire and satisfaction.